Survivors’ Stories of Sexual Assault on Campus - Davidson, Erin E.; Buchanan, Marla J. (Canadian Journal of Counselling and Psychotherapy, 2022)
Sexual assault is a common experience, with nearly 460,000 occurrences happening each year in Canada. Research suggests that women attending university are sexually assaulted at a higher frequency than the general population. Sexual assault (SA) has wide-ranging harmful physical, financial, social, and psychological impacts. Prevalence rates of SA are higher among women than men (30% versus 8%). Given the prevalence rates of SA, there is an urgent need for more research into the experiences of sexual assault, particularly in terms of knowledge from survivors of sexual assault on campus. A narrative research method was chosen for this study because it affords survivors of sexual assault the opportunity to construct a personal narrative and to give voice to their experiences. The research question for this study was: “What narratives are constructed by survivors of sexual assault on campus?” All the survivors were current students at a university in British Columbia and had experienced a sexual assault within the past 5 years. Six narrative themes emerged: (a) difficulty considering the experience as sexual assault, (b) harmful emotional consequences, (c) a hesitation to report and disclose experiences, (d) a placating or freeze response, (e) a desire to reconnect with the perpetrator, and (f) the need for education, resources, and policy changes on campus. The findings have significance for university sexual assault policies and procedures and offer valuable information for sexual assault counsellors in their practice.